Determiners and relative clauses - Benincà, Paola (IBERIA: An International Journal of Theoretical Linguistics, 2014)
In the present paper, I consider first the behaviour of singular count nouns, showing that, in the limited set of contexts in which they are found, a specific kind of modification is in many cases necessary. The modification is represented by a variant of a kind defining relative clause. I briefly outline the main syntactic and semantic characteristics of kind-defining relatives; I then consider bare plural count nouns and singular mass nouns; I use the Left Dislocation construction as a test that permits us to explore the composition of the DP, and to localise the position of a silent operator. I show that, in this context too, the modifiers that permit the determiner to be omitted can be semantically interpreted as corresponding to a kind-defining relative. Finally, I examine the so-called partitive DPs introduced by di+article, which are often considered in the literature to be semantically equivalent to bare nouns, and I show that they are instead different, both semantically and syntactically; incidentally, this permits us to point out a minimal difference between French and Italian.